2021
DOI: 10.1126/science.abf2155
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-scale heterostructured piezoelectric bio-organic thin films

Abstract: Piezoelectric biomaterials are intrinsically suitable for coupling mechanical and electrical energy in biological systems to achieve in vivo real-time sensing, actuation, and electricity generation. However, the inability to synthesize and align the piezoelectric phase at a large scale remains a roadblock toward practical applications. We present a wafer-scale approach to creating piezoelectric biomaterial thin films based on γ-glycine crystals. The thin film has a sandwich structure, where a crystalline glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 41 publications
3
181
1
Order By: Relevance
“…Improved means for converting mechanical energy to electricity are needed for diverse applications, from harvesting ocean wave energy to power cities to using body motion to power sensors and energystorage devices in and on the human body. [1][2][3][4][5][6] Recently described coiled carbon nanotube (CNT) yarns, called twistrons, [7] use stretch-induced changes in electrochemical capacitance to generate higher peak electrical power per harvester weight than generated by any prior-art mechanical energy harvester for mechanical frequencies between 6 and 600 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Improved means for converting mechanical energy to electricity are needed for diverse applications, from harvesting ocean wave energy to power cities to using body motion to power sensors and energystorage devices in and on the human body. [1][2][3][4][5][6] Recently described coiled carbon nanotube (CNT) yarns, called twistrons, [7] use stretch-induced changes in electrochemical capacitance to generate higher peak electrical power per harvester weight than generated by any prior-art mechanical energy harvester for mechanical frequencies between 6 and 600 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…High‐throughput phase‐field simulations are performed to analyze the effective properties of the BTO/PVA composites with versatile geometrical morphologies to design the optimal configuration with both excellent piezoelectric and mechanical properties. In this study, we choose PVA as the polymer matrix because PVA has good degradability, [ 42 ] stretchability, [ 43 ] biologically compatibility, [ 44 ] and self‐healing ability, [ 45 ] which makes it an excellent candidate material for biomedical applications. For the high‐throughput calculations, a set of 400 (20 × 20) composite architectures are generated simultaneously to form a computing dataset by tuning the geometric ratios a y / a z and a x /a z of oxide fillers ranging from 0.1–10, assuming that the oxide fillers randomly disperse in the polymer matrix with a constant volume fraction of 1 vol%.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Yang et al reported a self-assembly method to develop highly crystalline and selfaligned γ-glycine piezoelectric films. [49] PVA-glycine-PVA sandwich heterostructure assisted oriented growth of piezoelectric γ-glycine by forming strong hydrogen bonds between O-atoms in glycine and À OH on PVA chains. The films exhibited a piezoelectric response comparable to the other commercially available piezoelectric materials such as PVDF.…”
Section: Electroactive Phase Addition and Functionalizationmentioning
confidence: 99%